TRADISI MEMBUANG AYAM SAAT IRING-IRINGAN PENGANTIN PERSPEKTIF MADZHAB SYAFI’I: Studi Kasus Desa Ganjaran Gondanglegi Kabupaten Malang - Ulum, Bahrul; Asror , Khozinul (Ahwal Al-Syakhsiyyah Fakultas Syariah - Universitas Al-Qolam Malang, 2024)
The purpose of this research is to understand the extent of the practice of throwing chickens during the wedding procession to the bride's house. This is intriguing because, in an era of modernity, there are still communities that maintain this old tradition, including the residents of Ganjaran Village, Gondanglegi, Malang. This research uses a field study method with a phenomenological approach, collecting data through interviews. The findings of this research show that: 1) Many people do not understand the reason for throwing chickens into the river during the wedding procession. Some members of the community who practice it do not understand the reason for throwing chickens into the river during the wedding procession. They merely preserve or follow the commands of their ancestors. In practice, some community members throw chickens into the river during the wedding procession by tying a thread to the chicken's leg. Once released into the river, they pull the chicken back. However, this practice is not taught by their ancestors. 2) The law regarding throwing chickens into the river during the wedding procession is not explicitly detailed in the fiqh books. However, in the principles of fiqh, it is mentioned: العادة محكمة. Such a tradition is considered 'urf shahih, a customary practice that does not contradict Islamic texts. However, this tradition can become impermissible if it is intended for offerings or other similar purposes, even becoming haram.